1997
DOI: 10.1172/jci119550
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of an increase in plasma cortisol during hypoglycemia preserves subsequent counterregulatory responses.

Abstract: The aim of this study was to determine whether preventing increases in plasma cortisol during antecedent hypoglycemia preserves autonomic nervous system counterregulatory responses during subsequent hypoglycemia. Experiments were carried out on 15 (8 male/7 female) healthy, overnightfasted subjects and 8 (4 male/4 female) age-and weightmatched patients with primary adrenocortical failure. 5 d before a study, patients had their usual glucocorticoid therapy replaced with a continuous subcutaneous infusion of cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 46 publications
6
72
0
Order By: Relevance
“…Chronic elevation of glucocorticoid levels decreases basal catecholamine levels and reduces stress-induced catecholamine release, metabolism, turnover, and synthesis in the PVH (42). Glucocorticoids, which are released by each glucoprivic bout (43), have been implicated in the pathophysiology of impaired glucoregulation in HAAF (44,45). Our results reveal C1 through C3 to be potential sites in which glucocorticoids could act to produce a loss of sensitivity to a subsequent glucoprivic challenge.…”
Section: A B C D E Fmentioning
confidence: 68%
“…Chronic elevation of glucocorticoid levels decreases basal catecholamine levels and reduces stress-induced catecholamine release, metabolism, turnover, and synthesis in the PVH (42). Glucocorticoids, which are released by each glucoprivic bout (43), have been implicated in the pathophysiology of impaired glucoregulation in HAAF (44,45). Our results reveal C1 through C3 to be potential sites in which glucocorticoids could act to produce a loss of sensitivity to a subsequent glucoprivic challenge.…”
Section: A B C D E Fmentioning
confidence: 68%
“…In 1996, Davis et al (16) reported that nondiabetic human subjects receiving two 2-h cortisol infusions (2 g ⅐ kg Ϫ1 ⅐ min Ϫ1 or ϳ9 mg/h) exhibited blunted day 2 neuroendocrine responses to hypoglycemia. Lending further support to their cortisol hypothesis, these authors later reported that following day 1 hypoglycemia, patients with Addison's disease (who could not mount endogenous cortisol responses) had preserved day 2 counterregulatory responses to hypoglycemia (27). However, the latter study's findings were complicated by profoundly suppressed epinephrine responses (Ͻ200 pg/ml or Ͼ60% lower than the epinephrine responses from our control studies) in the Addison's patients, present even during the control studies; this may have limited the ability of antecedent hypoglycemia to exert an additional effect.…”
Section: Discussionmentioning
confidence: 83%
“…Diabetes is characterized by high glucocorticoid concentrations and a lack of circadian periodicity in HPA activity, which may underlie unresponsiveness of the axis to stress (22,29 -34). Davis et al (35)(36)(37) suggested that partial impairment of the HPA counterregulatory response is due to recurrent exposure to high cortisol levels during hyperinsulinemic-euglycemic clamps. However, our work indicated that repeated exposure to elevated corticosterone in the absence of hyperinsulinemia does not diminish the HPA counterregulatory response (38).…”
Section: Discussionmentioning
confidence: 99%